A Study on the Application of “Telling China’s Stories Well” to Ideological and Political Education in College English Courses - Fu, Chunxia (Journal of Educational Research and Policies, 2025)
In the new era of deepening international exchange and cooperation, “Tell China’s stories well” is essential for enhancing the cultural soft power of the country and spreading Chinese culture to the world. How to implement “telling China’s stories well” is a mission for the foreign language education. As carrying out the basic task of fostering virtue through education is the mission of higher education, “telling China’s stories well” is also a good path for ideological and political education. This paper mainly explores the application of “telling China’s stories well” to ideological and political education in college English courses. It analyzes the significance of this application and discusses the practical teaching process and strategy. Based on the practical teaching, interview and questionnaire survey, it shows that students have high evaluation on this teaching strategy. It is suggested that the application of “telling China’s stories well” to ideological and political education in college English courses can be feasible and effective. The comprehensive abilities of students are been improved, whether their English language proficiency, morality, or practical abilities.